Long-term impact of investments in early schooling: Empirical evidence from rural Ethiopia - Mani, Subha; Hoddinott, John F.; Strauss, John (International Food Policy Research Institute, 2010)
This paper identifies the cumulative impact of early schooling investments on later schooling outcomes in the context of a developing country, using enrollment status and relative grade attainment (RGA) as short- and long-run measures of schooling. Using a child-level longitudinal dataset from rural Ethiopia, we estimate a dynamic conditional schooling demand function where the coefficient estimate on the lagged dependent variable captures the impact of all previous periods' schooling inputs and resources. We find that this lagged dependent variable indicates a strong positive association between current and lagged schooling. Past history matters more for girls than boys and for children from higher-income households compared with the poor.